Cross-locational experiments to reveal yield potential and yield-determining factors of the rice cultivar 'Hokuriku 193' and climatic factors to achieve high brown rice yield over 1.2kg m-2 at Nagano in central inland of Japan. (3rd April 2022) - Okamura, Masaki; Hosoi, Jun; Nagata, Kenji; Koba, Kentaro; Sugiura, Daisuke; Arai-Sanoh, Yumiko; Kobayashi, Nobuya; Kondo, Motohiko
ABSTRACT: Understanding the yield potential and yield-determining factors of recent high-yielding cultivars is essential for further increasing rice yield. In this study, a cross-locational field experiment was conducted across 3 years using 'Hokuriku 193ʹ (H193), a high-yielding cultivar, at four sites including one in Nagano Prefecture, which is the highest-yielding region in Japan. The highest mean yields of 3 years, 1214 g m −2 for brown rice grains and 1586 g m −2 for rough grains, were recorded at the Nagano site. The yields from the 17 environments were strongly correlated with spikelet number per square meter while percentage of filled grain was relatively stable, suggesting that sink capacity is the primary determining factor for grain yield of H193. The climatic factors for high spikelet number at the Nagano site can be explained by the high cumulative radiation before heading associated with longer duration until heading by low night temperature. In addition, a large increase in shoot dry weight during grain filling (ΔW) and high radiation use efficiency (ΔW/rad) at the Nagano site could satisfy large source demand by the large sink size. The high ΔW/rad at the Nagano site associated with low night temperature. This study demonstrated high yield potential of H193 and revealed an environment that achieves extra-high yields in H193, which provided insight to attain further increase in rice yield. Graphical abstract: uf0001